Effect of Three Fibrate Derivatives and of Two HMG-CoA Reductase Inhibitors on Plasma Fibrinogen Level in Patients with Primary Hypercholesterolemia - Branchi, Adriana; Rovellini, Angelo; Sommariva, Domenico; Gugliandolo, Angelo G; Fasoli, Angelo (Thrombosis and Haemostasis, 1993)
In order to evaluate the effects of hypocholesterolemic drugs on plasma fibrinogen concentration, six groups of subjects with primary hypercholesterolemia have been put on treatment with diet alone or diet plus fenofibrate (100 mg t.i.d.), slow release bezafibrate (400 mg once a day), gemfibrozil (600 mg b.i.d.), simvastatin (20 mg once a day) or pravastatin (20 mg once a day) respectively. After 1 month of therapy, plasma fibrinogen significantly decreased by 9% and 15% in fenofibrate and bezafibrate groups respectively and increased by 19% in gemfibrozil treated patients. After 4 months of therapy the changes were −16% with fenofibrate, −10% with bezafibrate and +20% with gemfibrozil. No significant changes were observed in patients treated with diet alone, simvastatin or pravastatin. The fibrinogen lowering effect of fenofibrate and bezafibrate does not seem to be related to the hypolipidemic activity of the drugs.